Relationship between muscle morphological characteristics and joint torque exertion ability during movements simulating speed skating in junior and senior sprint speed skaters - Yuda, J.; Yanagisawa, O.; Murata, M.; Yokozawa, T.; Yamanobe, K.; Aoyanagi, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2011)
The purpose of this study was to identify the relationship between muscle morphological characteristics and joint torque exertion ability during movements simulating speed skating in sprint speed skaters. In 10 junior and 9 senior elite male skaters who participated in the 500-m race, the cross-sectional areas (CSA) of the right thigh and torso muscles were measured using magnetic resonance imaging. Skaters performed two dry skating tests (single leg skate jump and side-jump) on a tartan track, and were videotaped using two synchronized high-speed video cameras (250 fps) with the DLT technique during the tests. The ground reaction forces (GRF) of the support right leg were measured using a force platform (500 Hz). The GRF and three-dimensional coordinates of the segment endpoints were determined in order to calculate the maximal joint torques in the lower limb using an inverse dynamics approach. Although no significant difference in the CSA of the thigh was observed between the junior and senior groups, the CSA of the torso in the senior group was significantly greater than that in the junior group (p<0.01). In the torso, the CSAs of the psoas major and quadratus lumborum in the senior group were significantly greater than those in the junior group (p<0.01 and p<0.05, respectively). During the single leg skate jump, no significant difference in the maximal joint torques in the lower limb was observed between the junior and senior groups. In contrast, during the side-jump, the maximal hip abduction and internal rotation torques in the senior group were significantly greater than those in the junior group (p<0.05 and p<0.01, respectively), whereas maximal ankle plantar flexion torque in the junior group was significantly greater than that in the senior group (p<0.05). In addition, significant positive relationships were observed between the CSA of the quadratus lumborum and maximal hip abduction and internal rotation torques during the side-jump (p<0.05). These results indicate that senior top skaters increase their maximal joint torque exertion not at the distal joint but at the proximal joint in the lower limb. It was suggested that the CSAs of the psoas major and quadratus lumborum in the torso were important factors for development of performance in sprint speed skating.